Anti-icing epoxy resin surface modified by spray coating of PTFE Teflon particles for wind turbine blades. (March 2020) - Qin, Chao (Chris); Mulroney, Alan T.; Gupta, Mool C.
Highlights: Anti-icing epoxy resin surface was generated by a spray coating of PTFE particles. Static contact angle and roll-off angle were at 154° and below 2° respectively. The ice detachment strength was approximately 30 kPa on average. The coating method was demonstrated for scalability and wind turbine application. Abstract: Epoxy resins are widely used for the outer surface of wind turbine blades and many other engineering applications. An anti-icing epoxy resin surface was generated by a spray coating of polytetrafluoroethylene (PTFE; commonly known as Teflon) nanoparticles. The Teflon particles with a mean diameter of 300 nm were dispersed in acetone to achieve 5 % weight fraction. The static contact angle and the roll-off angle for deionized water were measured at 154° and below 2° respectively. The ice detachment strength at the temperature of −10 °C and 16 % relative humidity was approximately 30 kPa on average, which was about 2.5 % of the ice detachment strength of an aluminum substrate and was about 20 % of the ice adhesion strength of plain epoxy. This spray coating method has no limit on the application coverage surface area. To demonstrate the scalability of this coating method, a 101.6 mm by 101.6 mm aluminum surface was successfully produced in the laboratory and demonstrated the same superhydrophobic and icephobic surface characteristics as the smaller test surfaces.